2015
DOI: 10.1002/cne.23766
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the amyloid precursor‐like protein 1 (APLP1) enhances excitatory synaptic transmission, reduces network inhibition but does not impair synaptic plasticity in the mouse dentate gyrus

Abstract: Amyloid precursor-like protein 1 (APLP1) is a transmembrane synaptic protein belonging to the amyloid precursor protein (APP) gene family. Although the role of this gene family-in particular of APP-has been intensely studied in the context of Alzheimer's disease, the physiological roles of its family members remain poorly understood. In particular, the function of APLP1, which is predominantly expressed in the nervous system, has remained enigmatic. Since APP has been implicated in synaptic plasticity, we wond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In addition to the above discussed differences in APP levels, differences in APP processing and thus the abundance of specific fragments such as sAPPα between brain regions may also play an important role. Likewise, regional differences in the expression of APP-like proteins, i.e., APLP1 or APLP2, which can partially compensate for a loss of APP could affect the interpretation of loss-of-function experiments (von Koch et al, 1997; Heber et al, 2000; Weyer et al, 2011; Hick et al, 2015; Vnencak et al, 2015). Regardless of all these considerations, however, APP can only play a role in synaptic plasticity of a synapse if it is present.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above discussed differences in APP levels, differences in APP processing and thus the abundance of specific fragments such as sAPPα between brain regions may also play an important role. Likewise, regional differences in the expression of APP-like proteins, i.e., APLP1 or APLP2, which can partially compensate for a loss of APP could affect the interpretation of loss-of-function experiments (von Koch et al, 1997; Heber et al, 2000; Weyer et al, 2011; Hick et al, 2015; Vnencak et al, 2015). Regardless of all these considerations, however, APP can only play a role in synaptic plasticity of a synapse if it is present.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the behavioral paradigm it has been noted that depletion of APLP1 resulted in an improvement of acquisition learning. The in vivo analysis at the perforant path-granule cell synapse (PP-DG) in young adult mice (16–20 weeks old) revealed unaltered STP and LTP, associated to enhanced excitatory transmission (Vnencak et al, 2015). The authors argued that maybe a larger number of perforant path synapses or an increased synaptic strength in APLP1-deficient mice may cause this enhancement, but final clarification is missing.…”
Section: Role Of Full-length App Proteins At the Synapsementioning
confidence: 99%
“…Several studies suggest that the hyperactivity is caused by APP overexpression (Born et al, 2014) while others assume Aß to be the trigger (Busche et al, 2008; Minkeviciene et al, 2009). The APP family proteins seem to be closely involved in regulating GABAergic transmission as both APLP1-KO and aged APP-KO mice exhibit reduced GABAergic mediated PPD responses (Seabrook et al, 1999; Vnencak et al, 2015) and in addition increased susceptibility for kainite-induced seizures (Steinbach et al, 1998). Moreover, supporting the role of APP within the GABAergic network are the chronic reduction of GABA A receptors and the lowered number of GABA B autoreceptors mediating PPD of inhibition in the absence of APP (Fitzjohn et al, 2000) as well as the identified interaction of APP with GABA B receptors in vitro (Norstrom et al, 2010) as well as recently in vivo (Schwenk et al, 2016).…”
Section: Role Of the App Protein Family In Synaptic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to APP-KO mice, APLP1-KO mice show reduced body weight but normal locomotor activity and grip strength (Heber et al, 2000). Electrophysiological analysis of perforant path-granule cell synapses of the dentate gyrus revealed decreased network inhibition but no alterations in LTP in APLP1-KO mice (Vnencak et al, 2015). In line with this, morphological analysis of CA1 neurons in organotypic hippocampal cultures revealed normal spine density and dendritic branching (Weyer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%